Morphological Variations of Fissures of Lungs in Indian Population - VG Sawant, Joy Ghoshal, Manisha Nakhate, Ruta Bapat, (International Journal of Innovative Research in Medical Science, 2017)
Introduction: The lungs are the pair of essential organs of respiration located within the thoracic cavity, on either side of heart. Pulmonary interlobar fissures are important landmarks for proper identification of normal pulmonary anatomy and evaluation of disease. A pulmonary fissure is a boundary between the lobes in the lings. Its segmentation is of clinical interest as it facilitates the assessment of lung disease. Objectives: The purpose of this study was to define the morphological variations of fissures of lungs in Indian population. Material & Methods: Morphological variations of fissures such as complete or incomplete; presence of any variant fissure and accessory fissure of 80 lungs (40 right and 40 left) were studied. Results: Out of 40 right lungs, the horizontal fissure was absent in 5 lungs (12.5%) and incomplete in 4 lungs (10%). Oblique fissure was absent in one lung (2.5%) and incomplete in 3 lungs (7.5%). The complete absence of the horizontal and oblique fissures was reported in one lung (2.5%) and accessory fissures were present in 8 lungs (20%). Out of 40 left lungs, the incomplete oblique fissure was noted in one lung (2.5%) and accessory fissures were present in 5 lungs (12.5%). Conclusion: These variations are of radiological and surgical importance for assessment of lung disease.